The Final Season : The Perseverance of Pat Summitt - Cornelius, Maria M. (Book collections on Project MUSE., 2016)
With 1,098 wins and eight national championships, Lady Vol Coach Pat Summitt has left a remarkable legacy of perseverance, leadership, and passion for the game-but her victories on the court aren't the only legacy she has left in her wake.Since the beginning of her career as Lady Vol head coach at twenty-two years old, Pat Head Summitt effectively established the University of Tennessee Lady Vols as the top women's athletics program in the nation. The winningest coach in the history of NCAA basketball, Summitt overcame one obstacle after another on the road to every victory, but it is the live.